2008
DOI: 10.1002/cjoc.200890149
|View full text |Cite
|
Sign up to set email alerts
|

A One‐pot, Stereoselective Synthesis of (Z)‐2‐Sulfonyl‐Substituted 1,3‐Enynes by Hydrostannylation‐Stille Tandem Reaction of Acetylenic Sulfones

Abstract: (Z)-2-Sulfonyl-substituted 1,3-enynes can be stereoselectively synthesized in one pot by the palladiumcatalyzed hydrostannylation of acetylenic sulfones, followed by Stille coupling with alkynyl bromides. The present method has the advantages of readily available starting materials, straightforward and simple procedures, mild reaction conditions and good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Our group has reported the Stille coupling reactions of (E)-α-arylsulfanyl-or selenenyl-substituted vinylstannanes with organic halides in the presence of a catalytic amount of Pd(PPh 3 ) 4 and CuI cocatalyst, providing new methods for stereoselective synthesis of 1,2-disubstituted vinyl sulfides [20] and 2-selenenyl-substituted 1,3-and 1,4-dienes [21,22]. Very recently, we have found that (E)-α-arylsulfonylsubstituted vinylstannanes can also be coupled with aryl iodides or alkynyl bromides in the presence of Pd(PPh 3 ) 4 and CuI cocatalyst, to afford 1,2-disubstituted vinyl sulfones [23] and 2-sulfonylsubstituted 1,3-enynes [24], respectively. However, to the best of our knowledge, there has been no general study of the Stille coupling reaction of (E)-α-arylsulfanylvinylstannanes with acyl halides described to date.…”
Section: Introductionmentioning
confidence: 97%
“…Our group has reported the Stille coupling reactions of (E)-α-arylsulfanyl-or selenenyl-substituted vinylstannanes with organic halides in the presence of a catalytic amount of Pd(PPh 3 ) 4 and CuI cocatalyst, providing new methods for stereoselective synthesis of 1,2-disubstituted vinyl sulfides [20] and 2-selenenyl-substituted 1,3-and 1,4-dienes [21,22]. Very recently, we have found that (E)-α-arylsulfonylsubstituted vinylstannanes can also be coupled with aryl iodides or alkynyl bromides in the presence of Pd(PPh 3 ) 4 and CuI cocatalyst, to afford 1,2-disubstituted vinyl sulfones [23] and 2-sulfonylsubstituted 1,3-enynes [24], respectively. However, to the best of our knowledge, there has been no general study of the Stille coupling reaction of (E)-α-arylsulfanylvinylstannanes with acyl halides described to date.…”
Section: Introductionmentioning
confidence: 97%
“…The palladium-catalyzed cross-coupling reactions of terminal alkynes with sp2 halides/triflates, in the presence (Sonogashira-Hagihara alkynylation) [11] or in the absence (Heck alkynylation) [12] of a copper co-catalyst, are even more useful synthetically and have been extensively used in the stereospecific synthesis of conjugated enynes. [13] Conjugated enynes were also formed using a coupling reaction between alkenylzirconium compounds and alkynyl halides, [14] or by the palladium-catalyzed hydrostannylation of alkynyl esters, followed by Stille coupling with alkynyl halides, [15] or by the palladium-catalyzed coupling reaction of vinyl tosylate and terminal acetylenes. [16] Moreover, conjugated enynes can be also conveniently prepared by palladium-catalyzed cross-coupling reactions of terminal alkynes with β-halo-α,β-unsaturated ketones.…”
Section: Introductionmentioning
confidence: 99%